New Formulation to Synthetize Semiconductor Bi2S3 Thin Films Using Chemical Bath Deposition for Optoelectronic Applications - Carrillo, Amanda (2022)
Abstract: Anisotropic materials possess direction dependent properties as a result of symmetry within their structure. Bismuth sulfide (Bi2S3) is an important semiconductor exhibiting anisotropy due to its crystalline and stratified structure. In this manuscript we present a new and straightforward procedure to deposit Bi2S3 thin films on soda lime glass substrates by the chemical bath deposition (CBD) technique. We studied two fundamental parameters, the time to deposit a single layer and the total number of layers deposited. The single layer deposition time was varied between 70 and 100 min and samples were coated with a total of 1, 2, or 3 layers. It is important to note that a fresh aqueous solution was used for every layer. Visible and near infra-red spectroscopy, scanning electron microscopy, X-ray photoelectrons spectroscopy, and X-ray diffraction were the characterization techniques used to study the resulting films. The calculated band gap values were found to be between 1.56 and 2.1 eV. The resulting Bi2S3 deposited films with the new formulation showed uniform morphology and orthorhombic crystalline structure with an average crystallite size of 19 nm. The thickness of the films varied from 190 to 600 nm in direct correlation to the deposition time and in agreement with the number of layers. The XPS results showed the characteristic bismuth doublet centered around 164.11 and 158.8 eV corresponding with the presence of Bi2S3. The symmetry within the Bi2S3 structure makes it a strong anisotropic crystal with potential applications in optoelectronic and photovoltaic devices, catalysis, and photoconductors among others.